Pedestrian mobility and constraints in the dormitory suburbs of Agbowo and Orogun in Ibadan (2013)
The study examined the constraints faced by pedestrian movement in Agbowo and Orogun communities in Ibadan. These are dormitory suburbs to members of educational and commercial concerns with a rapidly growing population and inadequate infrastructural provision that has contributed to the deteriorating residential environment. A mean traffic volume of pedestrians per hour of 5296 was obtained in the pedestrian count for Agbowo and 1369 for Orogun. From these figures, a sample size of 106 and 27 was derived for the two communities respectively and respondents were interviewed by the administration of structured questionnaires using an accidental sampling technique. Trip characteristics of the respondents reveal that daily trip frequencies rank very high in both communities and these are to activity centres located at short distances within the communities. The waiting time at the various bus stops was found out to be a motivating factor to trek. However, identified constraints of pedestrian mobility include bad roads 86.8% and 92.6%; absence of pedestrian walkway 74.5% and 74.1% on street parking 59.1% and 77.8%, roadside trading 55.7% and 70.4% in Agbowo and Orogun respectively. The study recommends the incorporation of pedestrian walkway as an integral part of road design within the two communities, enforcement of the planning regulations with reference to development control and an urgent improvement on the communities road network to facilitate effective shared use with pedestrians.